نماذج من نصوص الوقف بالمصاحف الأثرية المحبسة على مساجد الجزائر في العهد العثماني - نايم, فيصل (My University, 2022)
ملخص: حظيت المساجد بعدد كبير من المصاحف المحبسة عليها بهدف القراءة فيها، باعتبار أن قراءة القرآن الكريم تعتبر من أهم أعمال التقرب إلى الله، وبناء عليه أصبحت عملية وقف المصاحف على المساجد من التقاليد الإسلامية التي يراد بها الثواب والأجر للواقف، علما أن المصاحف تعد من أقدم الأوقاف لأن مكتبات المساجد كانت بالدرجة الأولى مكتبات قرآنية. سنساهم من خلال هذا المقال في الكشف عن بعض الجوانب المتعلقة بالوقفيات كنمط من أنماط قيود بيانات التوثيق على نماذج من مصاحف الجزائر في الفترة العثمانية وما تحمله من مختلف الصيغ والمضامين الواردة في نص الوقف مع الدراسة والتحليل. Abstract: A large number of Qurans were confined to the mosques for reading given that reading the holly Quran is one of the key acts of getting closer to Allah. Accordingly, the process of confining Qurans to mosques became an Islamic tradition that sought to receive God’s reward. In fact, Qurans are among the oldest endowments since mosques’ libraries were primarily Quranic libraries. This article reveals some endowment aspects as a type of documentation data restrictions on examples of Qurans of the Algerian mosques during the Ottoman era with the study and analysis of forms and contents in the endowment text